Detrital and igneous zircon ages for supracrustal rocks of the Kyrgyz Tianshan and palaeogeographic implications - Rojas-Agramonte Y.; Kröner A.; Alexeiev D.V.; Jeffreys T.; Khudoley A.K.; Wong J.; Geng H.; Shu L.; Semiletkin S.A.; Mikolaichuk A.V.; Kiselev V.V.; Yang J.; et al. (My University, 2014)
We report detrital zircon ages for Precambrian and early Palaeozoic metasediments from the Tianshan orogen in Kyrgyzstan, an important component of the Central Asian Orogenic Belt and compare these with published ages from the Chinese Tianshan and the Tarim craton. These data provide information on possible source terrains and suggest that Precambrian basement is widespread in the Tianshan and may, at least in part, represent continental fragments rifted off the Tarim craton during the early history of the Central Asian Orogenic Belt Distinct differences in the Precambrian zircon age distribution between the North and Middle Tianshan of Kyrgyzstan support earlier ideas that these two terranes had different crustal histories prior to their amalgamation in the early Palaeozoic. We envisage an archipelago-type scenario for the Palaeo-Asian Ocean south of the Siberian craton in the late Neoproterozoic to early Palaeozoic in which numerous island arcs and Precambrian crustal fragments derived from Tarim drifted northwards (in present coordinates) and were amalgamated and tectonically stacked together during several ocean closure and accretion collision events. This is surprisingly similar to what has been envisaged for the evolution of Indonesia where Mesozoic rifting of fragments from the Australian margin was followed by Cretaceous collisions and Cenozoic collision of Australia with the SE Asian margin. In both Central Asia and Indonesia continental crust has arrived in the region in multiple episodes and has been fragmented and juxtaposed by subduction-related processes. Continental growth during this process was minimal.
Keywords: Kyrgyzstan; Tianshan; Detrital zircon age; Palaeo-Asian Ocean; Tarim craton